Future scenarios of the collaborative economy: Centrally orchestrated, social bubbles or decentralized autonomous?. (5th September 2018) - Fehrer, Julia A.; Benoit, Sabine; Aksoy, Lerzan; Baker, Thomas L.; Bell, Simon J.; Brodie, Roderick J.; Marimuthu, Malliga
Abstract : Purpose: The collaborative economy (CE), and within it, collaborative consumption (CC) has become a central element of the global economy and has substantially disrupted service markets (e.g. accommodation and individual transportation). The purpose of this paper is to explore the trends and develop future scenarios for market structures in the CE. This allows service providers and public policy makers to better prepare for potential future disruption. Design/methodology/approach: Thought experiments – theoretically grounded in population ecology (PE) – are used to extrapolate future scenarios beyond the boundaries of existing observations. Findings: The patterns suggested by PE forecast developmental trajectories of CE leading to one of the following three future scenarios of market structures: the centrally orchestrated CE, the social bubbles CE, and the decentralized autonomous CE. Research limitations/implications: The purpose of this research was to create CE future scenarios in 2050 to stretch one's consideration of possible futures. What unfolds in the next decade and beyond could be similar, a variation of or entirely different than those described. Social implications: Public policy makers need to consider how regulations – often designed for a time when existing technologies were inconceivable – can remain relevant for the developing CE. This research reveals challenges including distribution of power, insularity, and social compensation mechanisms that need consideration across states and national borders. Originality/value: This research tests the robustness of assumptions used today for significant, plausible market changes in the future. It provides considerable value in exploring challenges for public policy given the broad societal, economic, and political implications of the present market predictions.